Pengaruh Jumlah Kredit dan Suku Bunga Terhadap Pendapatan Usaha Mikro di BRI Unit Kabila - Amir Halid; Ria Indriani; Delvi Suleman (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2014)
This study aims to determine the development of the customer (Micro KUR and significant effect between credit amount and the interest rate on the income customers at BRI Unit Micro Kabila. Kind of research used in this study is a survey method. Data used are primary data interviews with customer respondents micro and secondary data from the BRI unit Kabila, the sampling method used was purposive sample, data collection techniques are methods of documentation and interviews. Data analysis technique used is multiple regression analysis and usingdescriptive statistics. Results from this research showed revenue that micro (Y) 63,7% total affected by credit (X1) and interest rate, while the remaining 36,3 %affected by other factors. R value of 0,798 means that income by the number of loans and interest ratest have a very strong positive relationship. T-test showed that the significant amount of credit, because the value is significantly smaller than the value 0,05 (0,000), while the interest rate effect is not real, because the value is significantly smaller than the value of 0,05 (0,874). For the development of the number of credits and the number of clients small loans (KUR) have increased and decreased each year. Keywords: Economic, credit, interest rates, UKM, income